Metastable vacuum decay and θ dependence in gauge theory. Deformed QCD as a toy model - Bhoonah, Amit; Thomas, Evan; Zhitnitsky, Ariel R. (Nuclear physics. B, 2015)
We study a number of different ingredients related to the θ dependence, metastable excited vacuum states and other related subjects using a simplified version of QCD, the so-called “deformed QCD”. This model is a weakly coupled gauge theory, which, however, preserves all the relevant essential elements allowing us to study hard and nontrivial features which are known to be present in real strongly coupled QCD. Our main focus in this work is to test the ideas related to the metastable vacuum states (which are known to be present in strongly coupled QCD in large N limit) in a theoretically controllable manner using the “deformed QCD” as a toy model. We explicitly show how the metastable states emerge in the system, why their lifetime is large, and why these metastable states must be present in the system for the self-consistency of the entire picture of the QCD vacuum. We also speculate on possible relevance of the metastable vacuum states in explanation of the violation of local P and CP symmetries in heavy ion collisions.